The Influence of Auditor Reputation, Firm Size, and Audit Delay on Financial Report Integrity - Ramadhanil, Ridho; Ridwansyah, Eksa; Rusmianto, Rusmianto (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the effect of auditor reputation, firm size, and audit delay on the integrity of financial statements of companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) during 2020–2023. Methodology/Approach: A quantitative approach was employed, utilizing secondary data from annual reports of LQ45 companies between 2020 and 2023. The sample, selected through purposive sampling, consisted of 41 companies (164 observations). Data analysis was conducted using multiple linear regression with classical assumption tests, using SPSS (version 27). Results/Findings: The results reveal that auditor reputation and firm size have a positive and significant impact on the integrity of financial statements, while audit delay has a negative and significant effect. Companies audited by reputable firms and those with larger assets tend to produce more reliable financial statements. In contrast, longer audit delays reduce the integrity of reports. Collectively, the three variables significantly influence financial statement integrity. Conclusions: The study concludes that auditor reputation and firm size positively affect the integrity of financial statements, while audit delay negatively impacts it. Companies with reputable auditors and larger sizes are more likely to produce trustworthy financial reports. These findings emphasize the importance of corporate governance and audit quality in ensuring financial transparency. Limitations: This study is limited to companies listed in the LQ45 index, using secondary data from 2020–2023, limiting generalizability. Contributions: The study provides empirical evidence on factors affecting financial statement integrity and offers insights for regulators, auditors, and investors to enhance reporting transparency.